Looking for professional identity of public health workers in Poland - Cianciara , Dorota; Sugay, Larysa; Rutyna , Anna; Urban, Ewa; Piotrowicz, Maria; Gajewska, Małgorzata; Lewtak, Katarzyna; Gotlib , Joanna (Polish Journal of Public Health, 2019)
Introduction. Public health is a specific field, which deals with an improvement of population health. It is an interdisciplinary and intersectoral activity and requires participation of various workers. All current documents and acts in public health field in Poland emphasize on the performance of specific tasks, but leave aside personal status and competencies. Many aspects were not resolved till now, e.g. which domains should be included in public health workforce, the problem of workforce enumeration: how large this group should be and what competencies should have. Aim. The aim of the study was an attempt to indicate some professional identity components for public health workers. Material and methods. The study was performed applying the semi-structured interviews method using a hermeneutic approach. The informants were a purposeful sample of 12 people who obtained the master’s degree in public health and already took up professional work and graduated from two universities. The basic research question was: how do interviewees perceive the public health worker? Results. All respondents, regardless of the place of work, perceived themselves as public health workers and presumably as specialists. Attempts to describe a public health worker led to non-specific and generalized statements. There were no answers revealed to the responsibility issue for effects of work among interviews. Respondents tended to characterize public health worker competencies vertically, by domain categories, not functionally, by public health services, so the issue of key competencies importance for identity is controversial. Conclusions. There are no strong evidences that particular workplaces or core competencies are related to professional identity of public health workers. Universities have an important role in professionalization of such workers